ANALISIS INDEKS GLIKEMIK PADA NASI CAMPURAN ANTARA BERAS (Oriza sp) DENGAN UBI JALAR ORANGE (Ipomoea batatas L) - fannisa izzati; Evawany Y Aritonang; Albiner Siagian (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2015)
Sweet potato rice is an alternative food are substituting rice with sweet potatoes. Orange sweet potatoes orange contents much β-carotene which is caused sweet potato rice as a kind of rice rich in antioxidants. Orange sweet potato can be processed into refined products, one of them into flour. Through the orange sweet potato flour can also be processed into orange sweet potato rice. The glycemic index is a blood glucose response to food compared with blood glucose response to pure glucose. The glycemic index is purpose for determining the blood glucose response to the type and amount of food consumed. The type of research used in this study is an experimental research, namely to produce rice from the rice with the addition of orange sweet potato flour with the ratio of one to one (1: 1). The purpose of this study was to determine the glycemic index food such as sweet potato rice test closer glycemic index rice or sweet potato glycemic index and how the velocity raise blood sugar levels after eating the test food. The composition of nutrients in orange sweet potato rice is water 52.6%, dust 0.29%, protein 4.74%, fat 0.57%, carbohydrate 41.2% and crude fiber 0.44%. The energy content contained on orange sweet potato rice amounting to 234.6 kcal. The results of this study indicate that the glycemic index is based on the measurement of orange sweet potato rice by using a reference food such as white bread showed that orange sweet potato rice has a glycemic index value of 83% and this figure is included in the category of food that has a high glycemic index value (> 70 ). Need to do further research on the glycemic index orange sweet potatoe rice with a composition ratio of the other as an ingredient in the produce of orange sweet potato rice and more further research on the measurement of glycemic index value of other processed foods made from sweet potato (Ipomoea batatas L). Keywords: nabilar, orange sweet potato flour, glycemic index